Analysis of The Side Effects of Dots (Directly Observed Treatment Shortcourse) on The Success of Pulmonary Tuberculosis (Tuberculosis) Therapy at Raa Soewondo Pati Hospital - Ummi Nur Faidah; Eko Retnowati; Galih Kurniawan (International Journal of Health and Pharmaceutical (IJHP), 2026)
This study aims to analyze the side effects of DOTS on the success of TB therapy. The research was conducted at the RAA Soewondo Pati Hospital using a quantitative descriptive method with a cross-sectional approach. Sampling was carried out using a total sampling technique, and 117 respondents were obtained who met the inclusion and exclusion criteria. Data collection was carried out through a questionnaire of side effects and medication adherence that has been tested for validity and reliability, and supported by patient medical record data. Data analysis includes univariate analysis, and bivariate analysis with Chi-square and Odd Ratio (OR) tests. The results showed that the most common side effects experienced by patients were urine discoloration to red (100%), flu syndrome (29.9%), nausea (18.8%), and no appetite (15.4%). The severity of the majority of side effects was in the mild category (88%). The patient compliance rate was relatively high, namely 92.3% complied in undergoing therapy, and 93.2% of patients were declared successful in completing therapy. The results of bivariate analysis showed that there was a very significant relationship and influence between drug side effects and the success of pulmonary tuberculosis therapy. This is shown by the results of the chi-square test  which shows  a p-value of 0.000 (p<0.05). And the Odd Ratio (OR) which yields a value of 0.010. Interpretation of this value shows that patients who experience moderate side effects have a 100-fold higher risk of therapy failure.